Identity Construction by Justice-Involved Homeless Women: An Exploration of the Role of Traumatic Experiences in the Process of Desisting from Crime and Housing Stabilization - Moffet-Bourassa, Mathilde; Marcotte, Julie; F.-Dufour, Isabelle (International Journal on Homelessness, 2026)
The experiences of justice-involved homeless women (JIHW) and the meanings they attach to these experiences are integral to their present and future identities. However, the ways individuals perceive and interpret their experiences are deeply embedded within cultural context, suggesting that certain experiences –and the social meanings attached to them –may play a central role in identity construction. Contemporary research has shown that individual characteristics subject to stigma can profoundly shape meaning-making processes essential to identity construction. For example, homelessness often leads to stigmatizing that may influence how individuals define themselves. In this qualitative study, the life narratives of five JIHW engaged in the dual process of exiting homelessness and desisting crime were analyzed to identify how they describe the influence of their traumatic experiences in the construction of their identity. The analysis shows that JIHW go through five identity positions asthey cope with traumatic experiences. Identity work articulated through these positions highlights how developing the capacity to make sense of traumatic experiences can support a clearer understanding of the self, which in turn can foster housingstabilization and desisting from crime.